Building blocks to develop your own Alumni engagement roadmap - Bray, Rachel; Grceva, Nena (ICAReAlumni Conference Proceedings, 2021)
1 Surveys and strategic goals ; 2 Building a case for support; 3 Alumni Engagement; 4 Building support across the institution; 5 Recognize, retain and expand; KPI, Metrics to evaluate program’s success